Morfogênese do testículo de embriões e fetos de vacas da raça nelore (Bos taurus indicus) - Jacomini, José Octavio; Esper, Cesar Roberto; Diniz, Elmo Gomes; Vieira, Rogerio Chaves; Beletti, Marcelo Emilio (My University, 2007)
The aim of this study was to accompany the process of testicular development from the non-differentiable phase to its complete formation. Embryos and fetuses of Nelore breed cows (Bos Taurus indicus) were obtained in slaughterhouses near the Uberlandia city, Minas Gerais. The gonads and the embryos were fixed in Bouin's fixative and afterwards processed for conventional optical microscopy. The gonadal was observed firstly in a 1.0 cm long embryo. In 2.5 cm long embryos the presence of the albuginea allows the sex identification. The mean thickness of the albuginea ranged from 29.08 to 558.45 mm. Gradually increase of vascularization of the albuginea and parenchyma is observed. The mediastinum is located centrally. There was a decrease in the space occupied by the testicular cords, from 63.71 to 41.99% of the total testes volume. Its diameter ranged from 31.68 to 48.80 mm. The diameter of germinal cells (and their nuclei) was from 12.27 (6.65) to 16.95 914.21) mm. The quantity of germinal cells by cross section of cord decreased from a maximum of 2.80 to 0.76. The total number of germinal cells was from 16 at the beginning of colonization of the gonad to 18.32 x 106 at the end of the study. The number of Sertoli's cells by cross section of cord ranged from 10.00 to 16.25. The results obtained show that the origin and formation of testes in embryos and fetuses from Nelore breed cows (Bos taurus indicus) does occur in a very similar way to what is described for Bos taurus taurus.
Morfogenesis of testis from embryos and fetuses of nelore breed cows (Bos taurus indicus)
Keywords: Albuginea; Bovines; Germinal cells; Gonad; Sertoli's cells; Bos indicus; Bos taurus